The biocathode of microbial electrochemical systems and microbially-influenced corrosion - Kim, Byung Hong; Lim, Swee Su; Daud, Wan Ramli Wan; Gadd, Geoffrey Michael; Chang, In Seop (ELSEVIER SCI LTD, 2015)
The cathode reaction is one of the most important limiting factors in bioelectrochemical systems even with precious metal catalysts. Since aerobic bacteria have a much higher affinity for oxygen than any known abiotic cathode catalysts, the performance of a microbial fuel cell can be improved through the use of electrochemically-active oxygen-reducing bacteria acting as the cathode catalyst. These consume electrons available from the electrode to reduce the electron acceptors present, probably conserving energy for growth. Anaerobic bacteria reduce protons to hydrogen in microbial electrolysis cells (MECs). These aerobic and anaerobic bacterial activities resemble those catalyzing microbially-influenced corrosion (MIC). Sulfate-reducing bacteria and homoacetogens have been identified in MEC biocathodes. For sustainable operation, microbes in a biocathode should conserve energy during such electron-consuming reactions probably by similar mechanisms as those occurring in MIC. A novel hypothesis is proposed here which explains how energy can be conserved by microbes in MEC biocathodes. (C) 2015 Elsevier Ltd. All rights reserved.